[OP.7A.01] THE GLOBAL SYMPLICITY REGISTRY: SAFETY AND EFFICACY REPORT. (September 2017) - Schlaich, M.; Boehm, M.; Mancia, G.; Schmieder, R.; Mahfoud, F.
Abstract : Objective: The aim of the Global SYMPLICITY Registry (GSR) is to collect real-world data on the safety and efficacy of renal denervation (RDN) using either the original Symplicity Flex (TM) renal denervation catheter or the newer-generation Symplicity Spyral (TM) catheter, which applies radiofrequency energy circumferentially to each renal artery quadrant simultaneously.Furthermore, following newer understanding of the renal anatomy, a sub-cohort of patients are receiving treatment of renal artery branch vessels in addition to the main renal artery. Design and method: The GSR is a prospective, multi-centre, non-randomized international registry of RDN enrolling up to 3000 patients with uncontrolled hypertension. Patients are followed at 3, 6, 12, 24, and 36 months. Follow up data collected per routine care includes: clinical assessment, office blood pressure measurement, 24-hour ambulatory blood pressure measurement, blood tests, ECGs, renal artery imaging, and EQ-5D quality of life questionnaire. At the time of ESH 2017 six month safety and efficacy data will be available for ∼2500 patients and 3-year data will be available on ∼1750 patients. Moreover, data from post-hoc analysis of ∼270 patients treated with the Symplicity Spyral catheter as well as data on ∼90 patients who had RDN treatment in both the main renal artery and branches will be available for presentation. Results: The Global SYMPLICITY Registry is the largest real world database of renal denervation therapy and has enrolled over 2500 patients to date. The registry also includes the largest dataset of renal artery branch treatment reported so far. All available follow-up data informing on short and long-term safety and efficacy of the Symplicity renal denervation system will be presented. Conclusions: These data supplement the randomized and sham-controlled SPYRAL HTN-ON MED and OFF MED trials evaluating safety and efficacy of renal denervation performed in the main renal artery and branch vessels in patients with uncontrolled hypertension.